Performance of a 48-in. Warm-oil Pipeline Supported on Permafrost - Rowley, R. K.; Watson, G. H.; Wilson, T. M.; Auld, R. G. (Canadian Geotechnical Journal, 1973)
An experimental pipeline loop, 2000 ft (609.8 m) long and 4 ft (1.22 m) in diameter, was constructed on the Mackenzie Valley Pipe Line Research Limited test site near Inuvik, N.W.T. Oil at 160 °F (71 °C) was circulated through the loop from February 1971 until January 1972 and performance of the continuous gravel berm and intermittent pile bent support systems and ice-rich permafrost foundation monitored.Instrumentation was placed on and around the pipeline to measure settlement and temperature. Site climatological data were also compiled. Settlement and other movements were monitored by periodically taking elevations at the ground surface and on survey rods attached directly to the pipe. Temperatures were measured using both resistance thermal device (R.T.D.) and thermistor type sensing elements. Measured changes in the foundation soil thermal regime were compared with performance as predicted by a two-dimensional thermal simulator model.The observed pipeline loop performance is discussed and compared with predictions for both foundation thawing and settlement. Applicability of the thermal simulator model used and the support piling behavior is also discussed.